The importance and effectiveness of cardiac screening in early diagnosis of critical congenital heart diseases (Annals of Medical Research, 2021)
Aim: Cardiac screening test for early diagnosis of critical congenital heart disease (CCHD) is recommended by our ministry of health in newborns. We wanted to investigate the effectiveness of the pulse-oximetry screening test recommended by the ministry of health in our neonatal intensive care unit. Our study is planned to find an answer to this question regarding the subject matter.Materials and Methods: Our study was planned retrospectively in cases followed up in our neonatal intensive care unit and obstetrics and gynecology clinic. Our study cases were accepted to the neonatal service of our hospital starting from 01/10/2015 in the 30-month period. Patients admitted from the neonatal and obstetrics / gynecology services were included in the study. Saturation measurements of these cases were made at the earliest 6th hour after birth. The test was considered positive, if saturation was